(untitled) (PANGEEA, 2025)
The community’s problems in the Apuseni Mountains were still inception Romanian rural sociology, a perpetual object of study. Sociological School of Bucharest had an important role in boosting research in the area by investigations carried out in 1937 in the village of Vidra. Knowledge, research, improvement and development of the countryside are vital activities for the country, both in terms of rural expressed by area owned and the population occupied in productive activities, social services, cultural, housing and tourism.